2011
DOI: 10.1007/s00395-011-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Activated NHE1 is required to induce early cardiac hypertrophy in mice

Abstract: The Na+/H+ exchanger isoform 1 (NHE1) has been implicated as being causal in cardiac hypertrophy and the protein level and activity are elevated in the diseased myocardium. However, it is unclear whether mere elevation of the protein is sufficient for cardiac pathology, or whether activation of the protein is required. In this study, we examined the comparative effects of elevation of wild type and activated NHE1. Two mouse transgenic models that expressed either a wild type NHE1 protein or an activated NHE1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 60 publications
5
44
1
Order By: Relevance
“…content [6]. The NHE1 activity contributes to cardiac hypertrophy [61,65,66,100]. Accordingly, cardiac hypertrophy and its progression to heart failure can be strongly reduced by NHE1 inhibitors [1,24,60].…”
Section: Discussionmentioning
confidence: 98%
“…content [6]. The NHE1 activity contributes to cardiac hypertrophy [61,65,66,100]. Accordingly, cardiac hypertrophy and its progression to heart failure can be strongly reduced by NHE1 inhibitors [1,24,60].…”
Section: Discussionmentioning
confidence: 98%
“…The cardiac Nhe1 has emerged as a key factor in myocardial remodeling [65,66,67]. Enhanced Nhe1 activity contributes to the pathophysiology of myocardial reperfusion injury [68], cardiac insufficiency [69] and cardiac hypertrophy [42,43,70,71,72]. Accordingly, upregulation of Nhe1 may trigger [73] and pharmacological inhibition of Nhe1 counteracts [65,66,67] cardiac hypertrophy and progression to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NHE1, and not increased expression of the protein per se, is the critical factor determining NHE1-mediated disease progression [55]. Further to this end, we recently demonstrated that replacement of endogenous NHE1 in MDA-MB-231 cells with a hyperactive NHE1 protein resulted in an increased metastatic behaviour of this cell line [14].…”
Section: Nhe1 and Signal Transduction Proteinsmentioning
confidence: 99%